Chromosomal abnormalities detected by karyotyping among patients with secondary amenorrhea: a retrospective study - Besson, Marina da Rocha; Taiarol, Mateus dos Santos; Fernandes, Eliaquim Beck; Ghiorzi, Isadora Bueloni; Nunes, Maurício Rouvel; Zen, Paulo Ricardo Gazzola; Rosa, Rafael Fabiano Machado (São Paulo Medical Journal, 2023)
BACKGROUND: Chromosomal abnormalities (CAs) have been described in patients with secondary amenorrhea (SA). However, studies on this association are scarce. OBJECTIVES: To evaluate the frequency and types of CAs detected by karyotyping in patients with SA. DESIGN AND SETTING: This retrospective study was performed in a reference clinical genetic service in South Brazil. METHODS: Data were obtained from the medical records of patients with SA who were evaluated between 1975 and 2022. Fisher’s bicaudate exact test and Student’s t-test were used, and P < 0.05 was considered significant. RESULTS: Among 43 patients with SA, 14 (32.6%) had CAs, namely del (Xq) (n = 3), 45,X (n = 2), 46,X,r(X- )/45,X (n = 2), 46,XX/45,X (n = 1), 46,X,i(q10)/45,X (n = 1), 47,XXX (n = 1), 46,XX/47,XXX (n = 1), 46,XX/47,XX- ,+mar (n = 1), 45,XX,trob(13;14)(q10;q10)/46,XXX,trob(13;14)(q10;q10) (n = 1), and 46,XX,t(2;21)(q23;q11.2) (n = 1). Additional findings were observed mostly among patients with CA compared with those without CA (P = 0.0021). No difference in the mean age was observed between the patients with SA with or without CAs (P = 0.268025). CONCLUSIONS: CAs are common among patients with SA, especially those with short stature and additional findings. They are predominantly structural, involve the X chromosome in a mosaic, and are compatible with the Turner syndrome. Patients with SA, even if isolated, may have CAs, particularly del (Xq) and triple X.